Obligation of Ownership of Taxpayer Identification Number (NPWP) and Taxable Entrepreneur Identification Number (NPPKP) for Taxpayers - Pratiwi Pratiwi; Fadhilah Syahrani Elpriyan; Putri Putri; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
In the Indonesian government, there is development that covers various aspects with the aim of realizing development, so the state requires self-assessment to register with the KPP to get NPWP and NPPKP. This research is formulated as follows: understanding of NPWP and NPPKP, sanctions for not registering NPWP, and NPWP as a means of tax administration. Sanctions for not registering NPWP and NPPKP, will result in administrative sanctions of 2% to 48%, in confinement for 6 months to 6 years, including a fine of twice the tax payable and the maximum amount of tax to be paid. As a result, sanctions can increase taxpayers' awareness of the importance of fulfilling their tax obligations.  According to Law Number 28 of 2007 Article 1 No. 6 Taxpayer Identification Number is a number given to taxpayers as a means in tax administration which is used as a personal identification or identity of taxpayers in carrying out their tax rights and obligations. Meanwhile, according to Resmi (2019) the Taxpayer Identification Number (NPWP) is a tool in tax administration that is used as a personal identification or identity of taxpayers.